Waist circunference references for children and adolescents from 6 to 18 year-old from the autonomous region of Madeira, Portugal - Sousa, Bruno; Mendes de Oliveira, Bruno; Nunes, José Luís; Vaz de Almeida, Maria Daniel (Nut. Food Sciences │ C. Nut. Alimentação, 2019)
Waist circumference (WC) has been associated with cardiometabolic diseases. We aim to develop WC references for age and gender in youngsters in Autonomous Region of Madeira, Portugal (RAM). A cross-sectional study was developed in two phases. Between May 2004 and May 2005 (in 1st cycle schools) and between October 2007 and June 2009 (in 2nd and 3rd cycle, and secondary and professional schools). A representative sample of 6987 individuals was gathered, with 3532 girls and 3455 boys aged from 6 to 18 years old. WC was measured with a non-elastic tape at the midpoint between the iliac crest and the last rib. To elaborate smoothed percentiles and z-scores curves for age and gender, values were estimated between 72 and 225 months (every three months) using the LMS statistical procedure, with the exponent of the Box-Cox (L), the median (M), and coefficient of variation generalized (S) through LMSChartMaker software, version 2.76. Mean and standard deviation and charts of smoothed percentiles curves (P3, P5, P10, P25, P50, P75, P85, P90, P95 and P97) and z-scores (-2, -1, 0, 1 and 2) are presented by age and gender. These references constitute a new tool to assess cardiometabolic risk of RAM's children and adolescents.

O perímetro da cintura (PC) tem sido associado a doenças cardiometabólicas. O objetivo deste estudo foi desenvolver referências antropométricas para o PC, em função da idade e sexo para uma população jovem da Região Autónoma da Madeira, Portugal (RAM). Este estudo transversal, foi realizado em duas fases - entre Maio de 2004 e Maio de 2005, nas escolas do 1.º ciclo, e entre Outubro de 2007 e Junho de 2009, nas escolas de 2º e 3º Ciclos , secundárias e profissionais. Esta amostra representativa de 6987 pessoas, inclui 3532 raparigas e 3455 rapazes dosos 6 a 18 anos. O PC foi avaliado com uma fita não extensível no ponto médio entre a crista ilíaca e a última costela. Para elaborar as curvas de percentis e z-scores suavizados para idade e sexo, os valores foram estimados entre 72 e 225 meses (a cada três meses) utilizando o procedimento estatístico LMS, através do software LMSChartMaker, versão 2.76. As médias e desvio-padrão, Figurae as curvas de percentis suavizados (P3, P5, P10, P25, P50, P75, P85, P90, P95 e P97) e z-scores (-2, -1, 0, 1 e 2) são apresentados por idade e sexo. Estas referências constituem uma nova ferramenta para avaliar o risco cardiometabólico de crianças e adolescentes da RAM.
Referências para o perímetro da cintura de crianças e jovens dos 6 aos 18 anos de idade da Região Autónoma da Madeira
Keywords: waist circumference; references; Madeira Island; Portugal; Região Autónoma da Madeira; percentiles; children; perímetro da cintura; crianças; adolescent; adolescentes